A High-Salt Diet Disturbs the Development and Function of Natural Killer Cells in Mice. (22nd December 2020) - Zeng, Xiaokang; Li, Yan; Lv, Weibiao; Dong, Xinhuai; Zeng, Chong; Zeng, Liming; Wei, Zibo; Lin, Xu; Ma, Yanning; Xiao, Qiang
Abstract : A high-salt diet (HSD) is common worldwide and can lead to cardiovascular disease, chronic inflammation, and autoimmune diseases. Moreover, increasing evidence shows that HSD is closely related to a variety of immune diseases. Natural killer (NK) cells are important innate immune cells that directly kill their targets via degranulation and secretion of interferon gamma (IFN- γ ). NK cells play a vital role in resisting viruses and preventing the malignant transformation of cells; however, whether HSD affects the development and function of NK cells has not yet been elucidated. Therefore, the purpose of the present study was to understand the effects of HSD on the development and function of NK cells, in addition to investigating the underlying molecular mechanism. Our results show that the number of NK cells in the spleen and lungs of HSD-fed mice was significantly reduced, which may be due to the inhibition of NK cell proliferation. Further, the development of NK cells in mice was evaluated, and it was found that HSD reduced the effective NK cell subset (CD27 + CD11b - ). Moreover, it was also found that the ability of NK cells to secrete CD107a and IFN- γ in HSD-fed mice was decreased following stimulation with RMA-S and YAC-1 tumor cells. Finally, the underlying molecular mechanism was evaluated, and it was found that HSD increased the production of reactive oxygen species (ROS) by NK cells, while the expression of CD122 was decreased, suggesting that HSD downregulates CD122 expression in NK cells via ROS signaling, thereby reducing the responsiveness to IL-15 and ultimately inhibiting NK cell function. The present research discovered a novel mechanism by which HSD inhibits the function of NK cells, providing an alternative avenue for the treatment of immune diseases caused by HSD.